The Effect of Taxes, Leverage and Bonus Mechanisms on Transfer Pricing Decisions - Farhan Fadil Ghifari; Cynthia Sari Dewi; Adven Filipi Baresi; Beryl Ezra Hutahuruk; Hanifah Pagar Alam (Journal of Accounting and Finance Management, 2026)
This study aims to examine the impact of taxes on transfer pricing practices, with leverage and bonus mechanisms included as control variables. Transfer pricing is a strategic issue for multinational companies engaging in transactions with related parties, as it may be used to shift profits and reduce tax burdens. This research employs a quantitative approach using multiple linear regression analysis. The study utilizes secondary data obtained from the annual financial statements of multinational companies listed on the Indonesian Stock Exchange for the period 2020–2024. Data analysis includes descriptive statistics, model feasibility testing using the F-test, hypothesis testing using the t-test, and evaluation of the coefficient of determination. The results indicate that taxes, proxied by Book Tax Difference, have a positive and significant impact on transfer pricing practices, suggesting that a larger gap between accounting profit and taxable profit increases the likelihood of transfer pricing. In contrast, leverage measured by the Debt to Equity Ratio shows a negative but statistically insignificant effect, while bonus mechanisms do not have a significant impact on transfer pricing. Furthermore, the coefficient of determination indicates that the explanatory power of the model is relatively low, implying that transfer pricing decisions are influenced by other factors beyond those examined in this study.